Land cadaster as an independent branch of scientific knowledge - Tretiak А.; Tretiak, V.; Panchuk, O.; Kovalyshyn, O.; Tarnopolskyi, A. (Land Management, Cadastre and Land Monitoring, 2018)
Problem setting. Experience of market land relations in Ukraine and in the Western developed countries demonstrates that land organization and land management as well as the State land cadaster constitute an informational-technical, multi-functional system, which is the most available for performance of the tasks. The system enables collecting, processing and supply of the reliable information about land parcels and subjects of legal land relations and its constituents are currently established in the country under the conditions of transition to market economic and land relations. The aim of the article is to argue land cadaster as an independent branch of scientific knowledge having its subject and methods of study. Main material. The science of land cadaster studies general peculiarities, principles and regularities, formation and performance of land parcels as objects of legal land relations, as a spatial basis and fixed assets of production in agriculture and forest husbandry and as a natural resource. Land cadaster is a system of information and documents, a complex of land-cadaster documentation, materials and information about legal structure of land fund, its distribution according to landowners, land-users, about quantitative characteristics and economic value of lands. Land cadaster is defined as a system of organizational and managerial actions and measures, actions and works of registration, accounting and evaluation of land parcels. Thus, the authors of the article consider that land cadaster is the only state multi-level system of land-cadaster works and the procedure to prove the fact of appearance or liquidation of land parcels as objects of property rights and the right to use and evaluate them. The system includes a complex of necessary data and documents concerning legal status of land parcels, their value and distribution between landowners, land-users, about the intended use of lands, as well as quantitative, qualitative and estimative characteristics of the land parcels. The system is one of the main mechanisms of state regulation of land relations, which are based on socially approved notions, economic and social-esthetic standards. Thus, the system of state land cadaster, performing national goals, enables implementation of those important actions in the field of legal relations, economy and land market. Considering the above-mentioned, the work gives a list of courses, which improve professional level of a land manager. Conclusions. In the process of evolutional development, land cadaster was transformed into a scientific course of a systemized knowledge about land fund, land resources, land parcels and the right for them, land use and its status, and land relations. It is a systemized knowledge about society, thinking, phenomenon or a process, which has a definite structure. It is a complex knowledge with internal and external relations and mutual dependencies, with its subject, object of study, which is determined by complexity and variety of the surrounding world. Key words: land cadaster, land-cadaster works, geographic informational system, science about land cadaster.